(untitled) (Docentes 2.0 Journal, 2025)
In the current educational context, students need to develop numerical skills and critical thinking to meet the challenges of the 21st century. Mathematical skills are fundamental for academic success, daily life, and professional development. The main objective of the research was to strengthen the mathematical skills of seventh-grade students in institutions in Catambuco, Pasto, by using critical thinking to propose and solve problems. Research was carried out within the holistic paradigm, holographic method, with a qualitative approach, interpretive type, propositional, and cross-sectional design. Surveys and questionnaires were applied to 120 students from Catambuco. The results were obtained through statistical analysis; a descriptive statistical analysis was performed with Microsoft Excel. The Spearman-Brown correlation was calculated using SPSS, obtaining a value of 0.785, which indicates a positive, high, and significant correlation, highlighting the need to implement an innovative teaching strategy based on critical thinking to strengthen numerical skills and prepare students to contribute significantly to society.